Hierarchical entropy analysis for flow pattern of steam-liquid two phase flow in a rod bundle - Zhang, Chao; Liu, Xinyue; Hou, Yandong; Li, Weichao; Cai, Benan; Cai, Weihua (Frontiers in Energy Research, 2023)
Flow pattern is very key parameter in the study of flow characteristics and heat transfer characteristics of two-phase flow. In this Paper, two-phase boiling experiment in a 3×3 rod bundle was conducted within the following parameter range: 0≤G≤600kg/(m2⋅s),0.1≤p≤0.12MPa,10≤ΔTsub≤30℃. We first observed the four typical flow patterns, including bubble flow, bubble-churn flow, churn flow, annular flow, and the physical characteristics were studied and the corresponding differential pressure fluctuation signals measured for the four typical flow patterns. The dynamic characteristic of typical flow pattern was investigated by the of hierarchical entropy algorithm. Then the hierarchical entropy value of different flow patterns was calculated. The results indicate that the hierarchical entropy has a better ability to resist noise, and can reveal dynamics complexity of different flow pattern in rod bundle.